2021
DOI: 10.1155/2021/5556659
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Mechanism and Effect of Camptothecin on Dextran Sodium Sulfate-Induced Ulcerative Colitis in Mice

Abstract: Camptothecin (CPT) is a cytotoxic quinoline alkaloid isolated from the bark and branches of the Chinese tree Camptotheca acuminata. CPT inhibits topoisomerase I. It possesses various antitumor activities and is mainly used in the treatment of colon, ovarian, liver, and bone cancers as well as leukemia. CPT inhibits the expressions of inflammatory genes and can prevent death from chronic inflammation. Therefore, we investigated the effect of CPT treatment in ulcerative colitis (UC) using DSS-induced UC mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…67 CPT inhibits the expressions of proinflammatory cytokines and improves ulcerative colitis induced by dextran sodium sulfate in terms of colon length and the disease activity index in rats. 68 In our experiment, we found that SCI induced downregulation of protein and mRNA expressions of Top-1, which may be result from SCI that rapidly leads to a large number of nerve cell death and immune microenvironment in early stage that inhibits cell proliferation and DNA replication in mice. Moreover, primary cultured neurons are difficult to proliferate, and OGD leads to obvious damage and death of primary cultured neurons.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…67 CPT inhibits the expressions of proinflammatory cytokines and improves ulcerative colitis induced by dextran sodium sulfate in terms of colon length and the disease activity index in rats. 68 In our experiment, we found that SCI induced downregulation of protein and mRNA expressions of Top-1, which may be result from SCI that rapidly leads to a large number of nerve cell death and immune microenvironment in early stage that inhibits cell proliferation and DNA replication in mice. Moreover, primary cultured neurons are difficult to proliferate, and OGD leads to obvious damage and death of primary cultured neurons.…”
Section: Discussionmentioning
confidence: 61%
“…CPT–bile acid conjugate alleviated sepsis‐induced liver injury by suppressing the NF‐κB signaling pathway 67 . CPT inhibits the expressions of proinflammatory cytokines and improves ulcerative colitis induced by dextran sodium sulfate in terms of colon length and the disease activity index in rats 68 . In our experiment, we found that SCI induced downregulation of protein and mRNA expressions of Top‐1, which may be result from SCI that rapidly leads to a large number of nerve cell death and immune microenvironment in early stage that inhibits cell proliferation and DNA replication in mice.…”
Section: Discussionmentioning
confidence: 99%
“…They can inhibit the expression of various cytokines, such as tumor necrosis factor (TNF)-α, IL-1β, IL-4, IL-6, IL-8, IL-12, IL-18, IL-22, and inducible nitric oxide synthase (iNOS) ( Zhao HM. et al, 2017 ; Li Y. et al, 2017 ; Zhao L. et al, 2017 ; Wang Y. et al, 2017 ; Huang et al, 2017 ; Sun et al, 2018 ; Wu et al, 2018 ; Lian et al, 2019 ; Ni et al, 2019 ; Yin et al, 2019 ; Liu et al, 2020 ; Wang Y. Z. et al, 2021 ; Yu et al, 2021 ).…”
Section: The Pathogenesis Of Ibdmentioning
confidence: 99%
“…Camptothecin, a quinoline alkaloid extracted from camptotheca acuminata , was also found to have therapeutic effects in mice with experimental IBD. Camptothecin may improve the expression of cellular inflammatory factors in mice with IBD by modulating clinical symptoms in IBD mice by modulating the expression of cellular inflammatory factors [ 210 ]. A recent review illustrated the great therapeutic potential of alkaloids of natural origin for UC [ 19 ].…”
Section: Nps With Ibd Therapeutic Activitymentioning
confidence: 99%